Effect of inlet and outlet size, battery distance, and air inlet and outlet position on the cooling of a lithium-ion battery pack and utilizing outlet air of cooling system to heat an air handling unit. (February 2022) - Mustafa, Jawed
Highlights: Cooling of a plate li-ion pack of batteries (LIPB) with 12 battery cells using airflow. Assessing the impact of using the outlet air from 5 LIPBs for heating an air handling unit. An increment in the inlet airflow reduces the temperatures of battery cell and outlet air. As the distance between the batteries is enhanced, air outlet temperature is intensified. 10.3 kWh of heating energy of building can be achieved from cooling system of batteries. Abstract: This paper evaluated the cooling of a plate li-ion pack of batteries (LIPB) with 12 battery cells using airflow. The LIPB is placed in a cooling chamber that is cooled by a forced flow of air passing through the battery cells. The impact of using the outlet air from 5 LIPBs of this type of battery for heating an air handling unit (AHU) is assessed. The variables include the input distance from the lower wall and the output distance from the upper wall, the input and output dimensions, as well as the distance between the battery packs, which are in the range of 0 to 1 meter, 0 to 0.8 m and 0 to 0.1 m, respectively. The amount of energy required for the residential unit in different months of the year for a cold and dry environment is estimated using the Carrier software. COMSOL Multiphysics software is also employed to simulate LIPB cooling. The heat transfer coefficient, the temperature of the batteries, the outlet temperature, and the pressure drop in the cooling system are determined by changing the size of the inlet and outlet of the airflow, the distance of the batteries from each other, and the change of the inlet and outlet location. The results reveal that an increment in the inlet airflow enhances the amount of pressure drop and heat transfer coefficient and reduces the value of battery cell temperature and outlet air temperature. As the distance between the batteries is enhanced, the pressure drop and air outlet temperature are intensified and the temperature of the battery cells is reduced. Also, it is observed that 10.3 kWh of the required heating energy of the building can be achieved from the outlet air from the cooling system of the batteries. Therefore, this system provides a maximum of 100% of heating energy in June and October and a minimum of 15% of the energy required for the house in October.